Voices of Emotion: Figurative Language and Identity Construction in Eminem’s Rap Lyrics - Ramadan Adianto Budiman; Dessy Dwijayanti (Translation and Linguistics (Transling), 2025)
This study endeavors to examine the employment of figurative language within the lyrics of Eminem’s songs from a stylistic perspective. Eminem’s lyrical prowess, characterized by its complexity and emotional depth, renders his work a compelling subject for linguistic inquiry. The research primarily focuses on the identification and critical analysis of various figures of speech—namely metaphor, hyperbole, alliteration, personification, and irony—utilized throughout a selection of his songs. Employing a qualitative descriptive methodology accompanied by textual analysis, the study reveals that figurative language functions as an expressive tool vital for the construction of self-identity, the articulation of past traumas, and the articulation of socio-cultural critique. The findings substantiate that Eminem’s use of figurative language not only exemplifies verbal creativity but also contributes significantly to the construction of identity and affect within the cultural framework of hip-hop.